Non-SUSY unification in left-right models (1999)
ABSTRACT: We explore in a model independent way the possibility of achieving nonsupersymmetric gauge coupling unification within left-right symmetric models, with the minimal particle content at the left-right mass scale which could be as low as 1 TeV in a variety of models, and with a unification scale M in the range 105 GeV ,M,1017.7 GeV.